The Effect of Rheumatic Gymnastics on Reducing Joint Pain in Elderly People With Rheumatoid Arthritis: A Literature Review - Sari, Nina Pamela; Maulana, Muhammad Rizki (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2025)
A person is said to be elderly when they reach the age of 60 and experience various changes. Elderly is the last stage of life growth. Rheumatoid arthritis is one of the causes of chronic disease and reduced motor function in the elderly which leads to musculoskeletal disease. One type of physical activity that can help overcome joint discomfort is rheumatic exercise. This study aims to ascertain whether rheumatic exercise can reduce joint discomfort in older adults suffering from rheumatoid arthritis. The four keywords “elderly” AND “rheumatic exercise” AND “pain” AND “rheumatoid arthritis” were used in this literature review, which was retrieved from research materials found in the Google Scholar database. Five journals related to the research topic were found. The findings of the five articles reviewed showed that rheumatic exercises are effective in lowering joint pain scores in older adults with rheumatoid arthritis. The majority of studies found that rheumatic exercises are effective in reducing joint pain scores in older adults suffering from rheumatoid arthritis. For future researchers, it is expected to expand the scope of references not only from Google Scholar.